Hubungan Efikasi Diri dan Motivasi Belajar Terhadap Hasil Belajar Berbasis E-Learning pada Mahasiswa Program Studi Pendidikan Matematika Universitas Flores - Suryani, Lely; Seto, Stefania Baptis; Bantas, Maria Goretty D. (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The objective of this study is to explore the correlation between self-efficacy and learning motivation towards the learning outcomes based on e-learning among the 4th semester students of mathematics education program, Universitas Flores. The research method used in this study was quantitative research with Linear Regression Analysis use of SPPS involving 40 students of the 4th semester randomly chosen. Data were collected through online questionnaire with Google Form. The Kolmogorov-Smirnov analysis and hypothesis testing with Bivariate Pearson Correlation through SPSS were used. The findings showed that self-efficacy (X1) and learning motivation (X2) had a positive impact towards learning outcomes based on e-learning (Y), as a result from the correlation analysis from R for X1 against Y= 0.895 and X2 against Y=0.923, and significant value between X1 and X2 against Y resulted with (**). Therefore, there was a positive influence with 1% significant. In the other words, the more increase or the better the self-efficacy and learning motivation are, the more increase the learning outcomes from the students.